Recent applications of microencapsulation techniques for delivery of functional ingredient in food products: A comprehensive review - Dwip Das Emon; MD. Sakibul Islam; Md. Anisur Rahman Mazumder; Mohammad Gulzarul Aziz; Md. Saydar Rahman (Food Chemistry Advances)
The COVID-19 pandemic has resulted in an increased consumer demand for functional foods, mostly due to their potential health benefits. Presently, there is a prevailing trend of incorporating microcapsules that contain functional components into food and beverages in order to develop functional foods. This work aims to present a comprehensive analysis of microencapsulation techniques and their utilization in the food and beverage industry, while also addressing the associated challenges and future possibilities. The review analyzes the manufacturing of functional or modified foods and beverages through various microencapsulation processes. These strategies involve incorporating bioactive compounds and probiotics into microcapsules or nanocapsules. In addition, the study also emphasized the influence of microencapsulation on the sensory characteristics of food, as well as the capacity of functional components to be absorbed and utilized by the body. Moreover, the discussion has highlighted the importance of microencapsulation, commonly used techniques in microencapsulation, the latest advancements in wall materials, and the growing need for functional food. The study concentrated on the difficulties linked to microencapsulation and its potential to be scaled up, and offered practical solutions for these issues. The study determined that microencapsulation of functional chemicals in foods and beverages is an innovative method for safeguarding delicate substances, regulating their release, enhancing sensory characteristics, and improving their bioavailability.